CORRELATION OF MUSCLE STRENGTH AND FUNCTIONAL CAPACITY IN ELDERLY AND PRACTITIONERS OF GYM LOCATED INSTITUTIONALIZED (Fiep Bulletin - online, 2011)
The elderly population is growing all over the world and many of these elderlys have no dependence in activities of daily living (ADLs). Therefore, the objective of this study was to compare the levels of muscular strength in active elderly and institutionalized elderly with muscle strength correlate with performance on selected tests of ADL. The sample was aged 19, 6 in the control group (CG) with a mean age of 75 and 13 elderly active (EA) with a mean age of 68 years and muscular strength were assessed by testing handgrip, speed chair lift (SCL), raising the floor (RF), put on socks (PS), normal walking speed (NWS) and maximum walking speed (MWS). The results show that active elderly have better performance in ADL compared with sedentary women. However, we found no correlation with muscle strength performance in selected tests of ADL. The possible reason for this outcome may not be the specificity of the handgrip with the selected tests, which uses the strength and muscle power in lower limbs.
Keywords: elderly; ADL; handgrip